The Shanghai Cooperation Organization Faces a Strategic Choice - Nurimbetov, Rakhmatulla (RA Journal of Applied Research, 2021)
In 2021, the Shanghai Cooperation Organization (SCO) will celebrate its 20-year anniversary. Transformed from the “Shanghai Five” mechanism on settlement of border disputes and confidence-building between four ex-soviet republics Russia, Kazakhstan, Kyrgyzstan, Tajikistan and China, into the full-fledged organization in 2001, has been become one of the important players in Eurasian region. Since then SCO has made significant progress, especially, in combating the threats of international terrorism, extremism and separatism and ensuring regional security in general. However, the SCO could not advance in the economic field that is a key for an integration and convergence of the members states with different political and economic systems. Moreover, rising tensions between some members, namely India and China, as well as pandemic crisis and current geopolitical uncertainties in Eurasia may further exacerbate the situation within the Organization. What path can the SCO take in the future? Will its agenda have changes? Will there be institutional reforms in the organization? What will be the role of the SCO in shaping the new multipolar world order and in the region? These are the questions, which are now circulating around the SCO.